Preterm Birth Is Associated With Depression From Childhood to Early Adulthood - Upadhyaya Subina; Sourander Andre; Luntamo Terhi; Matinolli Hanna-Maria; Chudal Roshan; Hinkka-Yli-Salomäki Susanna; Filatova Svetlana; Cheslack-Postava Keely; Sucksdorff Minna; Gissler Mika; Brown Alan; Lehtonen Liisa (Elsevier, 2022)
Objective:  There have been inconsistent findings on the associations between prematurity, poor fetal growth and depression. We examined the associations between gestational age, poor fetal growth and depression in individuals aged 5 to 25 years.
Method:  We identified 37,682 cases based on ICD-9 code 2961 and ICD-10 codes F32.0-F32.9 and F33.0-F33.9 from the Care Register for Health Care, and 148,795 matched controls from the Finnish Central Population Register. Conditional logistic regression examined the associations between gestational age by each gestational week, poor fetal growth and depression. The associations were adjusted for parental age and psychopathology, paternal immigrant status, maternal substance abuse, depression, number of previous births, marital status, socio-economic status, smoking during pregnancy and the infant's birthplace.
Results:  In the adjusted models, increased risk of depression was found in children born ≤ 25 weeks (1.89, 1.08-3.31), at 26 weeks (2.62, 1.49-4.61), at 27 weeks (1.93, 1.05-3.53) and ≥ 42 weeks (1.11, 1.05-1.19). In girls, extremely preterm birth was associated with depression diagnosed at 5 to 12 years (2.70, 1.83-3.98) and 13 to 18 years (2.97, 1.84-4.78). In boys, post-term birth (≥42 weeks) was associated with depression diagnosed at 19 to 25 years (1.28, 1.07-1.54). Poor fetal growth was associated with an increased risk of depression in full-term infants (1.06, 1.03-1.10) and post-term infants (1.24, 1.08-1.43).
Conclusion:  Preterm birth before 28 weeks of gestation appeared to play a role in the development of childhood depression. Smaller effects were also seen in post-term births, especially in boys.